A new species of Stethelmis Hinton (Coleoptera: Elmidae) from Argentina and description of its larva - MARTÍNEZ-ROMÁN,NICOLÁS RAFAEL (2019)
Abstract: A new species of Stethelmis, S. shepardi sp. nov., is described for Patagonia, Argentina from adults of both sexes. A full description and illustrations of both the adult and the larva of the new species are provided with comments on its habitat and distribution. Adults of the new species are compared with those of S. kaszabi (Hinton 1970) and S. chilensis (Hinton 1945). The larva of S. shepardi is compared with that of S. kaszabi, the other Stethelmis larva described. We also describe and illustrate for the first time the male genitalia of S. kaszabi. A key to the known species of Stethelmis is also included.